Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1063/1.4960498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phonon interference through long range interatomic bonds on thermal interface conductance

Abstract: We investigate the role of two-path destructive phonon interference induced by interatomic bonds beyond the nearest neighbor in the thermal conductance of a silicon-germanium-like metasurface. Controlled by the ratio between the second and first nearest-neighbor harmonic force constants, the thermal conductance across a germanium atomic plane in the silicon lattice exhibits a trend switch induced by the destructive interference of the nearest-neighbor phonon path with a direct path bypassing the defect atoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These layered structures are considered as a thermal bridge between the bulk liquid and the nanoparticles and hence increase the thermal conductivity of the nanofluid [56]. In addition, the heat in the crystalline solids is carried by phonons that are formed randomly, propagate in random direction, and are scattered via defects or by colliding each other [226][227][228]. Moreover, clustering of particles was found to influence the effective thermal conductivity [228].…”
Section: Effective Thermal Conductivitymentioning
confidence: 99%
“…These layered structures are considered as a thermal bridge between the bulk liquid and the nanoparticles and hence increase the thermal conductivity of the nanofluid [56]. In addition, the heat in the crystalline solids is carried by phonons that are formed randomly, propagate in random direction, and are scattered via defects or by colliding each other [226][227][228]. Moreover, clustering of particles was found to influence the effective thermal conductivity [228].…”
Section: Effective Thermal Conductivitymentioning
confidence: 99%
“…Detail discussion of the mechanism of various resonance effects can be learned also from the series of modeling works on atomistically controlled structures [199][200][201]. Han et al employed MD wave packet simulations and revealed that a single crystal plane of heterogeneous atom arrays embedded in a host crystal can strongly impede phonons of a specific frequency [199].…”
Section: Resonance Effect By Embedded Nanoparticlesmentioning
confidence: 99%